PRESERVASI KOLEKSI MUSHAF AL-QURAN DI MUSEUM BAYT AL-QURAN : DINAMIKA MUSHAF AL-QUR’AN DAN PRESERVASINYA DI MUSEUM BAYT AL-QUR’AN - Lili Sudria Wenny; Mauidlotun Nisa; Muhammad Shodiq; Hendrizen Hendrizen (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2023)
This study aims to reveal the extent of the efforts to preserve the Bayt Al-Quran Museum in maintaining the sacred collection of the Al-Quran Mushaf. This research is qualitative research using historical and political approaches. The historical approach is used to reveal the development and dynamics of the Al-Quran Mushaf in Indonesia. The political approach is used to see the extent of the government's role in supporting Al-Quran culture with the establishment of Al-Quran museums in Indonesia and the Indonesian Standard Mushaf. The primary data in this study is the collection of Al-Quran manuscripts at the Bayt Al-Quran Museum. While the secondary data of this research is authoritative literature that examines relevant topics in the form of oral information, books, articles, and news as well. Primary data were collected through field observations at the Baytul Quran Museum in Jakarta. From the findings and discussion above, it can be concluded that the Museum reflects the nation's culture, as well as the Bayt Al-Quran Museum which is clear evidence of the high Islamic and Al-Quran culture that is touched with Indonesian culture. Therefore, the existing culture must be preserved with preservation efforts through conservation and so on so that its existence can be enjoyed by all generations from year to year. Preservation of the collection of Al-Quran manuscripts is the same as the preservation in the library because the material being protected is the same, namely paper which has the potential to be damaged by time.